ANALISIS PENGARUH ENVIROMENTAL PERFORMANCE DAN SIZE TERHADAP NET PROFIT MARGIN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2013 2015 - Trias Madanika Kusumaningrum (BISMA (Bisnis dan Manajemen), 2018)
This study aimed to analyze the influence of Environmental Performance, SIZE, and Corporate Social Responsibility to the net profit margin and the difference between the influence of the Environmental Performance and Corporate Social Responsibility SIZE as an intervening variable.The samples were registered manufactories on BEI, with total amount of samples (n) were 93 with pooling data method from 2013 to 2015. Sample was taken using purposive sampling method based on particular criteria which was appropriate with research purposes.The results showed that the Environmental Performance (EP) significant negative effect on Corporate Social Responsibility (CSR), Size significant negative effect on Corporate Social Responsibility (CSR), Environmental Performance (EP) significant positive effect on net profit margin (NPM), Size does not effect on the net profit margin (NPM), Corporate Social Responsibility (CSR) has no effect on net profit margin (NPM), Corporate Social Responsibility (CSR) in the first model did not prove to mediate Environmental Performance (EP) to Net Profit Margin (NPM), and Corporate Social Responsibility (CSR) in the second model is not proven to mediate Size to Net Profit Margin (NPM).